Recoverable platinum bis(fluoro-ponytailed) bipyridine complex as catalyst for hydrosilylation of alkynes under thermomorphic condition. Issue 51 (22nd December 2016) - Lu, Norman; Chung, Wei-Cheng; Chiang, Hsing-Fang; Fang, Yung-Cheng; Liu, Ling-Kang
Abstract: The fluorous PtCl2 [5, 5′-bis-(n-C11 F23 CH2 OCH2 )-2, 2′-bpy] complex (2 ) was prepared and employed as recoverable catalyst for the hydrosilylation of alkynes. Pt-catalyst 2 with F-content 0.53 was recovered under the thermomorphic method by design and the catalyst was demonstrated capable of re-usage for 8 times without loss of activity. The leaching of Pt in product mixture was monitored, with ICP-MS, to be at as low as 10 −6 level per cycle in the 5-decyne reactions and at 10 −3 level per cycle in the (HO)CMe2 CCH reaction. The reaction-catalyst fulfills the principle of green chemistry, and with its addition nature the hydrosilylation delivers 100% atom economy. The easily prepared polyfluorinated (2, 2′-bpy)Pt complex 2 is the robust and thermally stable catalyst, which doesn't require specific handling for utilization and storage in laboratory. Graphical abstract: Highlights: Pt-catalyst 2 with F-content 0.53 was easily recoverable under the thermomorphic method. Pt complex 2 is the robust and thermally stable catalyst. The leaching of Pt was monitored by ICP-MS to be as low as 10 −6 level per cycle. The reaction-catalyst fulfills the principle of green chemistry, and the hydrosilylation delivers 100% atom economy.